Retesting the psychometric characteristics of the European cancer research and treatment organization’s quality of life questionnaire palliative care 15 Turkish version (EQRTC QLQ C15-PAL) and evaluating the influencing factors - Tugba Yavuzsen; Zeynep Sevgen Guc; Ozlem Ugur; Murat Bektas; Ilhan Oztop (Journal of Oncological Sciences)
Purpose: The study aimed to retest the reliability and validity of the European Organization for Research and Treatment of Cancer-Core Quality of Life-15 Items Questionnaire for Palliative Care (EQRTC QLQ-C15-PAL) for the Turkish society and examine the influencing factors. Methods: The study was conducted in cancer patients who applied palliative treatment in the Dokuz Eylul University Oncology Institute Medical Oncology Division between May of 2014 and January of 2015. The demographic data collection form, performance status, and the EQRTC QLQ-C15-PAL scale were employed in order to gather data. Results: A total of 164 patients completed the study. The total Cronbach's alpha value for the scale was 0.794. The mean scores including the overall questionnaire, and subscales, which were calculated after two measurements conducted at an interval of three weeks, presented a statistically significant difference (p < 0.01). Patients with higher and lower ECOG scores had significant differences in terms of total QLQ-C15-PAL questionnaire scores as well as its subscales of physical, emotional functioning (PF, EF), and fatigue (FA) (p < 0.05). The statistically significant differences between patients' ECOG scores and QLQ-C15-PAL total score, and PF, EF, FA, and pain (PA) scores were 0.375, 0.439, 0.245, and 0.221, respectively (p < 0.001). The QLQ-C15-PAL questionnaire is able to measure 94.0% of the factors measured by the QLQ-C30-PAL. The variables included in the model affected the patients' quality of life to the extent of 44.0%. Conclusion: It has been shown that the scale is a valid/reliable instrument to detect the quality of life of Turkish cancer patients. Keywords: Cancer, Palliative care, Quality of life